Horse kicks, flying bombs and potsherds: statistical theory contributes to archaeological survey. - Orton, Clive (Archaeology International, 2006)
In the application of statistics in archaeology, it is essential to choose an appropriate statistical model for the specific archaeological problem being addressed. This article discusses the application of statistical models to large-scale archaeological field survey and describes the development of software (sherdnav) designed to guide field walkers to where they should look next, once they have surveyed all the primary spots in a block, and its application to the Noviodunum Archaeological Project (NAP).